Obtenção, caracterização e estudo in vitro da atividade citotóxica e, ou, leishmanicida de novos complexos de rutênio (II) e (III) contendo hidroxibenzofenonas e 1-hidroxi-9,10-antraquinona - Dias, Júlia Scaff Moreira (2021)
The development of new metal complexes for therapeutic purposes is highlighted in the scientific community. In this perspective, the present work describes the synthesis, characterization and in vitro study of the cytotoxic and leishmanicidal activity of new ruthenium (II) and (III) complexes containing hydroxybenzophenones and 1-hydroxy- 9,10-anthraquinone. Series 1 is composed of six complexes with the general formula cis-[RuCl2(HB)(dppb)] where HB = HB1 = 2-hydroxy-4-(octyloxy)benzophenone (1), HB2 = 2-hydroxy-4- methoxybenzophenone (2), HB3 = 2,2'-dihydroxy-4,4'- dimethoxybenzophenone (3), HB4 = 2,2'-dihydroxy-4-methoxybenzophenone (4), HB5 = 2,4-dihydroxybenzophenone (5), HB6 = 2,4,4'-trihydroxybenzophenone (6) and dppb = 1,4-bis(diphenylphosphinebutane). While series 2 is constituted by two complexes of general formula cis-[RuCl2(HQ)(dppb)] (7) and trans-[Ru(HQ)(PPh3)2(bipy)]PF6 (8), where HQ = 1-hydroxy-9,10-anthraquinone, PPh3 = triphenylphosphine and bipy = 2,2- bipyridine. The complexes were characterized using the following techniques: elemental analysis, thermal analysis, molar conductivity, infrared, ultraviolet and visible absorption spectroscopy, 1H, 13C{1H} and 31P{1H} nuclear magnetic resonance spectroscopy, X-ray diffraction by single and polycrystals and cyclic voltammetry. Molecular modeling studies were used to evaluate the structures of the complexes obtained and to predict possible isomers, as well as to assist in the assignment of the bands observed in the UV-vis spectroscopy. The stability of the complexes in solution was evaluated for 48 hours and later, in vitro assays against the promastigote form of Leishmania amazonensis, showed greater leishmanicidal activity for (8) (IC50 = 2,2 μM), however its high cytotoxicity against macrophages (CC50 = 0,5 μM and IS = 0,2) made it impossible to continue the studies. In contrast, three (HB4, HB5 and HB6) of the six hydroxybenzophenones used showed results comparable to reference drugs in the treatment of the disease. The complex (8) showed more promising cytotoxic potential against the melanoma-derived CHL-1 lineage (IC50 = 14,50 μM, CC50 = 105,9 μM and IS = 7,3) and its interaction with DNA and human serum albumin were investigated.